The Importance of Forgiveness in Psychological Therapy and Personal Development - Sava, Nicu-Ionel (New Trends in Psychology, 2024)
Forgiveness is an essential process of emotional release, in which a person lets go of resentment and anger to achieve a state of well-being and inner balance. In psychological therapy, forgiveness is used to improve mental health, reduce stress, and facilitate personal growth. This article explores the benefits of forgiveness, its stages and the therapeutic support needed, based on international and Romanian research. The importance of forgiveness for physical health, reducing anxiety and developing empathy is highlighted, thus contributing to healthy personal development and more harmonious relationships.